The THE DEVELOPMENT OF PSYCHOSOCIAL CHARACTERISTICS IN JOHN STEINBECK’S “THE PEARL” - Aziiz Putrayuda; Thohiriyah (English Literature Department, Faculty of Economics, Law, and Humanities, 2024)
This study examines the characteristics of main characters of John Steinbeck's work